Levels of vitamin A, C, E with malondialdehyde in blood and milk serum in sub clinical mastitic cows - Kaygusuzoglu, Erdal; Yildiz, Hamit; Karatas, Fikret (My University, 2012)
The aim of this study was to determine serum and milk concentrations of vitamins A, C andE with Malondialdehyde (MDA) in with and without subclinical mastitic cows. The study was performed on 15 healthy and 23 subclinical mastitic cows, aged 4-9 years. The California Mastitis Test (CMT) was performed. Fiveteen udder belonging to 15 cows which gave negative reaction in CMT were considered to be healthy. Thirty two udder quarters belonging to 23 cows which gave positive reaction as CMT +1 and +2 were diagnosed to be affected by subclinical mastitis. Vitamin A, C and E levels in blood serum and milk samples were determined by spectrophotometry, MDA levels were analysed with High Performance Liquid Chromatography (HPLC). There was no significant difference in blood serum vitamin A and E levels between healthy and subclinical mastitic cows. However, vitamin C (p?0.01) and MDA (p?0.05) levels in subclinical mastitic cows were significantly lower than healthy cows. There was no significant difference in milk samples Vitamins A, E and MDA levels between healthy and subclinical mastitic cows but vitamin C levels in subclinical mastitic cows were significantly lower than healthy cows (p?0.01). In conclusion, serum and milk vitamin C with serum MDA levels of healthy cows were determined significantly higher than subclinical mastitic cows but there was no difference in serum and milk vitamin A and E with milk MDA levels between healthy and subclinical mastitic cows. © Medwell Journals, 2012.
Keywords: Cow; Lipid peroxidation; Mastitis; Milk samples; Turkey; Vitamins